2023
DOI: 10.1001/jama.2023.19574
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastrointestinal Adverse Events Associated With Glucagon-Like Peptide-1 Receptor Agonists for Weight Loss

Mohit Sodhi,
Ramin Rezaeianzadeh,
Abbas Kezouh
et al.

Abstract: This database study examines the association between glucagon-like peptide 1 agonists (eg, semaglutide, liraglutide) used for weight loss and reports of gastrointestinal adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 6 publications
(7 reference statements)
1
37
0
1
Order By: Relevance
“…Phentermine/topiramate might be attractive to those with insufficiently treated migraine headaches, since topiramate is FDA approved for this condition. NuSH-BTs appear to confer an elevated relative risk of serious gastrointestinal complications, including pancreatitis, gastroparesis, and ileus, although absolute risk is low. Therefore, they should be used with caution in patients with a history of these disorders.…”
Section: Adjunctive Aomsmentioning
confidence: 99%
“…Phentermine/topiramate might be attractive to those with insufficiently treated migraine headaches, since topiramate is FDA approved for this condition. NuSH-BTs appear to confer an elevated relative risk of serious gastrointestinal complications, including pancreatitis, gastroparesis, and ileus, although absolute risk is low. Therefore, they should be used with caution in patients with a history of these disorders.…”
Section: Adjunctive Aomsmentioning
confidence: 99%
“…Adverse events from these medications such as gastroparesis, increased risk for ileus and perioperative aspiration have been reported. Other retrospective studies and meta‐analysis have documented other adverse events such as pancreatitis, and gallbladder/biliary disease, 127–130 however these have been controversial due to their retrospective nature and other limitations. Delayed GE from GLP‐1 RAs has been documented in multiple studies, 21,98,121,122,124–126,131 including a systematic review and meta‐analysis of almost 25,000 patients included in 60 trials of GLP‐1 RAs showed association of risk difference of nausea with absolute excess weight loss over placebo 93 .…”
Section: Glp‐1 Ra Risks and Implications In Clinical Practicementioning
confidence: 99%
“…A recent study was conducted in Canada with a large heath claims database that captured outpatient prescriptions of 16 million patients in the U.S.; 4757 using liraglutide or semaglutide were compared with 654 using bupropion/naltrexone, and it showed an increased risk of pancreatitis with hazard ratio (HR): 9.09 [95% CI: 1.25–66], bowel obstruction HR: 4.22 [95% CI: 1.02–17.40], and gastroparesis HR: 3.67 [95% CI: 1.15–11.90], but not biliary disease in the GLP‐1 agonists group compared to bupropion/naltrexone 130 …”
Section: Glp‐1 Ra Risks and Implications In Clinical Practicementioning
confidence: 99%
“…JAMA publishes articles on research methods to advance the types of science that is important for clinical medicine, as well as commentaries and narrative essays to put the science in context. In the list of top-viewed and top-cited articles from 2023, all of these article types are represented: clinical trials and observational research studies in neurology, cardiology, infectious diseases, psychiatry, endocrinology, genetics, trial emulation methods, and more; editorials and commentaries, including a Viewpoint on the crisis of US child mortality rates; a narrative essay “Death by Patient Portal”; and clinical reviews on glioblastoma and other brain cancers, heart failure with preserved ejection fraction, autism spectrum disorder, and surgical site infections …”
Section: Top-viewed and Top-cited Articles From 2023mentioning
confidence: 99%